2012 Oceans 2012
DOI: 10.1109/oceans.2012.6404955
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the physical drivers of wave runup from a continuously operating terrestrial laser scanner

Abstract: A dune-mounted terrestrial laser scanner was used to investigate the physical drivers of runup on an intermediate beach under a variety of wave conditions. Specifically, the laser is automated to collect hourly, simultaneous observations of beach morphology and hydrodynamics in the swash and inner surf-zone. A strong tidal signal in de-tided runup statistics is observed such that the 2% exceedence runup elevation and mean swash elevation is higher at high tide than at low tide for the same given wave condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Only a few field experiments have used laser-scanner technology to perform similar types of measurements as that reported here Brodie et al, 2012;Almeida et al, 2013), and, as a consequence, very little is known about specific aspects, such as behaviour of the laser measurements for different angles of incidence. The variability in the laser-scanner output was investigated for different angles of incidence during a period where no morphological changes occurred to provide insight into the vertical resolution of the data (Fig.…”
Section: Deployment and Data Analysis Using A Laser Scannermentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few field experiments have used laser-scanner technology to perform similar types of measurements as that reported here Brodie et al, 2012;Almeida et al, 2013), and, as a consequence, very little is known about specific aspects, such as behaviour of the laser measurements for different angles of incidence. The variability in the laser-scanner output was investigated for different angles of incidence during a period where no morphological changes occurred to provide insight into the vertical resolution of the data (Fig.…”
Section: Deployment and Data Analysis Using A Laser Scannermentioning
confidence: 99%
“…Recent studies reporting the use of laser-scanners on natural beaches Brodie et al, 2012;Almeida et al, 2013) and laboratories (Blenkinsopp et al, 2012) have demonstrated the ability of the laser technology to measure swash hydrodynamics, as well as bed evolution, on the swash event time scale remotely (i.e., without the need to deploy the instrument within the region of interest). The versatility and precision of 2D laser-scanners have enabled the development of a large range of useful non-contact measurement applications ranging from medicine (e.g., Pallejà et al, 2009), forestry (e.g., Miettinen et al, 2007), to robotics (e.g., Vásquez-Martín et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Setup in the swash zone also has been measured using video-based tracking of the water-beach intersection (Holman and Sallenger 1985). More recently, processes in the swash zone have been observed with laser techniques (Blenkinsopp et al 2010;Brodie et al 2012;Almeida et al 2013;Vousdoukas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The water surface elevation is measured directly, and thus attenuation through the water column need not be considered (as it is for nearbed sensors), and sand-level changes can be measured when the beach is uncovered by swashes. Laser scanners accurately measure the subaerial beach topography in and shoreward of the swash zone in large-scale laboratory (Almeida et al 2013;Vousdoukas et al 2014) and field (Brodie et al 2012) studies. Lidar estimates of swash heights and excursions agree well with pressure and video estimates (Blenkinsopp et al 2010;Almeida et al 2013;Vousdoukas et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Remote sensing methods emerge in this context as the most appropriate solution for this type of field measurement, and recent developments on the use of 2D laser-scanners (Blenkinsopp et al, , 2012Brodie et al, 2012;or Almeida et al, 2013) to perform high frequency measurements of swash zone dynamics (including morpho and hydrodynamics) have demonstrated to be one of the most adequate tool for this propose.…”
Section: Introductionmentioning
confidence: 99%